The Potential of Photoacoustic Imaging in Radiation Oncology - Lefebvre, Thierry L.; Brown, Emma; Hacker, Lina; Else, Thomas; Oraiopoulou, Mariam-Eleni; Tomaszewski, Michal R.; Jena, Rajesh; Bohndiek, Sarah E. (Frontiers in Oncology, 2022)
Radiotherapy is recognised globally as a mainstay of treatment in most solid tumours and is essential in both curative and palliative settings. Ionising radiation is frequently combined with surgery, either preoperatively or postoperatively, as well as with systemic chemotherapy. Recent advances in imaging have enabled precise targeting of solid lesions yet substantial intratumoural heterogeneity means that treatment planning and monitoring remains a clinical challenge as therapy response can take weeks to manifest on conventional imaging and early indications of progression can be misleading. Photoacoustic imaging (PAI) is an emerging modality for molecular imaging of cancer, enabling non-invasive assessment of endogenous tissue chromophores with optical contrast at unprecedented spatio-temporal resolution. Preclinical studies in mouse models have shown that PAI could be used to assess response to radiotherapy and chemoradiotherapy based on changes in the tumour vascular architecture and blood oxygen saturation, which are closely linked to tumour hypoxia. Given the strong relationship between hypoxia and radio-resistance, PAI assessment of the tumour microenvironment has the potential to be applied longitudinally during radiotherapy to: detect resistance at much earlier time-points than currently achieved by size measurements; and tailor treatments based on tumour oxygen availability and vascular heterogeneity. Here, we review the current state-of-the-art in PAI in the context of radiotherapy research. Based on these studies, we identify promising applications of PAI in radiation oncology and discuss the future potential and outstanding challenges in the development of translational PAI biomarkers of early response to radiotherapy.